The relationship between water production rate and resistivity in sand-based porous materials under two-phase fluid flow and its application - Xie, Weibiao; Yin, Qiuli; Dai, Xueping; Fan, Yang; Zhang, Pan (Frontiers in Earth Science, 2025)
Accurately predicting the water production rate of multiple-phase fluid flows through porous rock is important for many engineering and geological applications. Taking into account irreducible water and capillary tortuosity, the equivalent rock element model from previous studies has been improved. Based on the improved capillary equivalent rock element model, this study proposes a relationship model between the water production rate in two-phase fluid systems and the resistivity index. The relationship model is verified using rock samples, and the result shows that the water production rate calculated by the new model closely matches experimental values, improving parameter calculation accuracy. In addition, applications of the new model to well logging data show that the calculated water production rate is consistent with the actual production situation. This approach is more efficient and accurate in reservoir evaluation. The new model provides a new idea for studying the seepage characteristics of rocks with multiple-phase fluids.